The Princeton Dictionary of Buddhism, by Robert E. Buswell, Jr and Donald S. Lopez, Jr - Forsthoefel, Thomas A. (Religions of South Asia, 2015)
The Princeton Dictionary of Buddhism, by Robert E. Buswell, Jr and Donald S. Lopez, Jr. Princeton, NJ: Princeton University Press, 2014. xxxii + 1265 pp. 65.00. ISBN 978-0-69115-786-3 (hardback).